Meta‐signature guided investigation of miRNA candidates as potential biomarkers of oral cancer. (16th March 2022) - Stojkovic, Goran; Jovanovic, Ivan; Dimitrijevic, Milovan; Jovanovic, Jasmina; Tomanovic, Nada; Stankovic, Aleksandra; Arsovic, Nenad; Boricic, Ivan; Zeljic, Katarina
Abstract: Objectives: This study aimed to experimentally validate dysregulated expression of miRNA candidates selected through updated meta‐analysis of most commonly deregulated miRNAs in oral cancer and to explore their diagnostic and prognostic potential. Materials and methods: Five miRNAs ( miR‐31‐3p, miR‐135b‐5p, miR‐18a‐5p, miR‐30a‐5p and miR‐139‐5p ) from updated meta‐signature were selected for validation by qRT‐PCR method in 35 oral cancer clinical specimens and adjacent non‐cancerous tissue. Results: Updated meta‐analysis has identified 13 most commonly deregulated miRNAs in oral cancer. Seven miRNAs were consistently up‐regulated ( miR‐21‐5p, miR‐31‐3p, miR‐135b‐5p, miR‐31‐5p, miR‐424‐5p, miR‐18a‐5p and miR‐21‐3p ), while five were down‐regulated ( miR‐139‐5p, miR‐30a‐3p, miR‐375‐3p, miR‐376c‐3p and miR‐30a‐5p ). Increased expression of miR‐31‐3p and miR‐135b‐5p, and decreased expression of miR‐139‐5p and miR‐30a‐5p were confirmed in oral cancer compared to adjacent non‐cancerous tissue. A three miRNAs combination ( miR‐31‐3p, miR‐139‐5p and miR‐30a‐5p ) gave the most promising diagnostic potential for discriminating oral cancer from non‐cancerous tissue (AUC: 0.780 [95% CI: 0.673–0.886], p < 0.0005, sensitivity 94.3%, specificity 51.4%). High expression of miR‐135b‐5p, miR‐18a‐5p and miR‐30a‐5p was associated with poor survival ( p = 0.003, p = 0.048, p = 0.016 respectively). Conclusion: miR‐31‐3p, miR‐139‐5p and miR‐30a‐5p panel was confirmed as a potential diagnostic biomarker when distinguishing oral cancer from non‐cancerous tissue. miR‐135b‐5p, miR‐18a‐5p and miR‐30a‐5p might serve as potential biomarkers of poor survival of oral cancer patients.